Exploring Scientific Literacy in Science Classrooms: A Literature Study - Yanto, Nurfitra; Nur Indah Sari; Yahya (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
Scientific literacy is a crucial competency for students in the 21st century, particularly in the context of science education. However, international assessments such as PISA continue to indicate that Indonesian students’ scientific literacy remains below global standards. This literature study aims to investigate the development, implementation, and impact of scientific literacy-oriented science learning in Indonesian schools by reviewing 20 selected articles published in accredited national journals. The review method involves analyzing research trends, learning models, and key factors influencing scientific literacy from studies conducted between 2016 and 2022. The findings show that various innovative learning models, including STEM-based learning, problem-based learning, guided inquiry, blended learning, and the use of digital teaching materials, have been widely applied to enhance students' scientific literacy. Most studies emphasize the effectiveness of integrating scientific literacy with critical thinking, character education, and environmental awareness. Moreover, student worksheets (LKPD), e-modules, and multimedia resources were found to support literacy development effectively, especially when aligned with scientific practices and real-life contexts. The review also identifies gaps in longitudinal studies, integration across different science disciplines, and limited focus on the primary education level. In conclusion, the literature reveals a strong movement toward designing science learning that not only builds scientific knowledge but also promotes students’ ability to apply it meaningfully in daily life. Further research is recommended to evaluate the long-term impact of these approaches and to develop integrated frameworks for enhancing scientific literacy across educational levels.